The Influence of Viral Marketing and Online Customer Review on Consumer Purchase Interest on Tiktok Social Media (Case Study on Mie Gacoan): PENGARUH VIRAL MARKETING DAN ONLINE CUSTOMER REVIEW TERHADAP MINAT BELI KONSUMEN PADA MEDIA SOSIAL TIKTOK (STUDI KASUS PADA MIE GACOAN) - Fauziah Zalza Sabillah; Taufik Akbar; Nining Latianingsih (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2022)
This study aims to determine and analyze whether there is a partial and simultaneous influence between viral marketing and online customer reviews on consumer buying interest. In addition, this research is expected to be a material consideration for Mie Gacoan in paying attention to viral marketing and online customer reviews. Therefore, consumer buying interest will increase. This research is included in causal associative research using a quantitative approach. This study uses a non-probability sampling technique using purposive sampling method. The number of samples taken as many as 100 respondents. Testing the instrument using validity and reliability tests. The data analysis method used is multiple linear regression, coefficient of determination test (R2), T test and F test. Data processing in this study was carried out using SPSS 26 software for windows. Based on the partial correlation results, viral marketing variables have an influence on consumer buying interest by 64.16% and online customer review variables have an influence on consumer buying interest by 54.76%. Based on the analysis of the coefficient of determination (R2), it was obtained that 71.2% of consumers' buying interest in gacoan noodles was influenced by independent variables, namely viral marketing and online customer reviews. Keywords: Viral Marketing, Online Customer Reviews, Consumer Buying Interest